Implementation of the Internal Quality Assurance System of Research Standards and Community Service of the University of Muhammadiyah Mamuju - Rasyid, Rohsita Amalia; Arsyad, Muhammad (Riwayat: Educational Journal of History and Humanities, 2025)
The background of this research is that the Muhammadiyah Central Leadership issued a Guideline Book for the Internal Quality Assurance System of Muhammadiyah Higher Education which was carried out in stages, systematically, planned, and directed, driven by the Quality Assurance Institute (LPM). The purpose of this quality assurance is to realize a culture of quality in the implementation of daily routine activities of the entire academic community. The fact that during the 26 years of the birth of the forerunner of Muhammadiyah University of Mamuju shows the inability of the institution to develop its quality through obtaining a higher Accreditation Ranking. This is evidenced by the value of the Institutional Accreditation acquisition being at Rank C from the National Accreditation Board for Higher Education. The Research and Community Service Section has always been a source of problems and notes for the Institution to always be improved because the value obtained in this section is still very minimal overall. Based on this description, it is very interesting to conduct research on "Implementation of the Internal Quality Assurance System in Research and Community Service at Muhammadiyah University of Mamuju". The purpose of the research is to determine the implementation of the internal quality assurance system of the Research and Community Service section at Muhammadiyah University of Mamuju. The results are expected to be a reference for compiling Institutional regulations in improving the Quality of Education and as a reference material for the contribution of further researchers' thoughts. This research method uses qualitative, a research method based on the philosophy of positivism, used to research natural object conditions, (as opposed to experiments) where the researcher is the key instrument. Data collection techniques are carried out through observation, interviews, questionnaires and documentation. Sampling is done purposively, namely the technique of determining samples with certain considerations. The independent variable in this study is building a culture of quality, while the dependent variable is the implementation of the internal quality assurance system for the Research and Community Service section. Data analysis uses descriptive statistical analysis. The results of this study indicate that the implementation of the internal quality assurance system at the Muhammadiyah University of Mamuju is still in the high category. Support in improving internationally accredited journals, indexed by Scopus. In essence, research and community service on an international scale still need to be improved.